The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.3390/ijms25042167
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of MicroRNA MiR-145 and MiR-155 Downstream Targets in Oral Cancers Exhibiting Limited Chemotherapy Resistance

Conner Belnap,
Tyler Divis,
Karl Kingsley
et al.

Abstract: New evidence has suggested that non-coding microRNAs play a significant role in mediating and modulating chemotherapy resistance, particularly among oral cancers. One recent study found that the upregulation of miR-145 and the downregulation of miR-155 strongly correlated with a limited chemotherapy resistance to Cisplatin, 5-Fluorouracil, and Paclitaxel, although the mechanism(s) responsible for these observations remain unidentified. Using commercially available cell lines of oral squamous cell carcinoma, RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…The primary goal of this project was to assess previously identified downstream targets of miR-365 to determine any potential associations with oral cancer phenotypes and to identify potential pathways of interest. This study successfully confirmed differences in phenotypes between commercially available oral cancer cell lines, with more chemoresistance observed among SCC25 and SCC9 cells and more chemosensitivity among SCC15 cells [23,24]. In addition, miR-365 expression was more highly correlated with SCC25 and SCC9 cells, as well as CAL27 cells, suggesting that pathways associated with this microRNA may be involved with these observed differences [21,22].…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The primary goal of this project was to assess previously identified downstream targets of miR-365 to determine any potential associations with oral cancer phenotypes and to identify potential pathways of interest. This study successfully confirmed differences in phenotypes between commercially available oral cancer cell lines, with more chemoresistance observed among SCC25 and SCC9 cells and more chemosensitivity among SCC15 cells [23,24]. In addition, miR-365 expression was more highly correlated with SCC25 and SCC9 cells, as well as CAL27 cells, suggesting that pathways associated with this microRNA may be involved with these observed differences [21,22].…”
Section: Discussionsupporting
confidence: 74%
“…All cells were maintained in Dulbecco’s Modified Eagle’s Medium (DMEM:F12) with the addition of 10% fetal bovine serum (FBS) and 1% penicillin-streptomycin antibiotic obtained from Fisher Scientific (Fair Lawn, NJ, USA). Cells were maintained in 25 cm 2 tissue culture-treated flasks in a biosafety level two (BSL2) cabinet with supplemental CO 2 at 5%, as previously described [ 21 , 22 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations